2022
DOI: 10.3389/fgene.2022.812674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alteration, Prognostic and Immunological Role of Acyl-CoA Synthetase Long-Chain Family Member 4 in a Pan-Cancer Analysis

Abstract: Acyl-CoA Synthetase long-chain family member 4 (ACSL4) is a member of acyl-CoA synthetase protein long-chain family, which is associated with amino acid synthesis, lipid synthesis and lipid peroxidation dependent iron death. However, the role of ACSL4 in generalized carcinoma remains unclear. We aim to analyze the expression and prognostic value of ACSL4 in pan-cancer, and further explore the correlation between ACSL4 and immune infiltration. Through ONCOMINE, TIMER (Tumor Immune Estimation Resource), GEPIA (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…According to a systematic study of the Oncomine and UALCAN databases, compared with normal tissues, ACSL4 is downregulated in breast cancer (BC), bladder cancer, brain cancer, leukemia, and lung cancer (LC), but upregulated in liver cancer, colorectal cancer, head and neck cancer, myeloma, ovarian cancer, and kidney cancer [116,117] . In addition, a comprehensive analysis of PrognoScan, the Kaplan–Meier mapping database, and Gene Expression Profiling Interactive Analysis revealed that low ACSL4 expression generally predicts a good prognosis across cancers despite the poor prognostic results in several certain cancers [117] . In addition, ACSL4 is negatively correlated with deoxyribonucleic acid (DNA) methylation levels and positively correlated with immune infiltration in most cancers [117] .…”
Section: Acsl4 In Human Diseasesmentioning
confidence: 99%
“…According to a systematic study of the Oncomine and UALCAN databases, compared with normal tissues, ACSL4 is downregulated in breast cancer (BC), bladder cancer, brain cancer, leukemia, and lung cancer (LC), but upregulated in liver cancer, colorectal cancer, head and neck cancer, myeloma, ovarian cancer, and kidney cancer [116,117] . In addition, a comprehensive analysis of PrognoScan, the Kaplan–Meier mapping database, and Gene Expression Profiling Interactive Analysis revealed that low ACSL4 expression generally predicts a good prognosis across cancers despite the poor prognostic results in several certain cancers [117] . In addition, ACSL4 is negatively correlated with deoxyribonucleic acid (DNA) methylation levels and positively correlated with immune infiltration in most cancers [117] .…”
Section: Acsl4 In Human Diseasesmentioning
confidence: 99%
“…Qin et al (2021) reported that SLC7A11 was associated with prolonged survival time of endometrial cancer, which suggested a protective factor. While CDKN1A was found to be an activator of ferroptosis, which was significantly associated with better prognosis of endometrial cancer (Yamawaki et al, 2017); and ACSL4 was associated with lipid metabolism and lipid peroxidation dependent ferroptosis, while the low expression of ACSL4 was -miR-146a-5p, hsa-mir-708-5p, hsa-miR-4746-5p, hsa-miR-452-5p, hsa-miR-452-3p, hsa-miR-224-5p, hsa-miR-375-3p, hsa-miR-30a-5p, hsa-miR-598-3p, hsa-miR-335-3p, hsa-miR-30c-5p, hsa-miR-101-5p, hsa-miR-210-3p ,hsa-miR-676-3p, hsa-miR-130a-3p, hsa-miR-1266-5p, hsa-miR-1271-5p ,hsa-miR-130a-5p, hsa-miR-203b-3p, hsa-mir-3074-5p, and hsa-miR-30d-5p Risk score = hsa-miR-146a-5p * 0. observed in endometrial cancer to be associated with better prognosis (Yu et al, 2022). Intriguingly, quite a few research studies have probed into the regulated mechanism of ferroptosis-associated genes in endometrial cancer, as indicated by the evidence that ferroptosis-associated genes were positively related to M1 macrophages, M2 macrophages, T cell follicular helper, and B cells naive, while they were negatively related to NK cells activated, T cells regulatory (Tregs) and neutrophils ; and that damage-associated molecular patterns (DAMPS) released by ferroptosis were sensed by the immune cells, thus enhancing inflammatory responses and improving the immune microenvironment in cancer was found (López-Janeiro et al, 2021).…”
Section: Ferroptosis and Prognosis Of Endometrial Cancermentioning
confidence: 95%
“…[26,67] ACSL4 expression is linked to immune cell infiltration. [68] IFN-γ secreted by CD8 + T cells and AA were shown to promote ACSL4-mediated ferroptosis. [69] Therefore, the relationship between ACSL4-mediated ferroptosis and immune infiltration and the impact on the efficacy of antitumor therapy should be the focus of future studies.…”
Section: Ferroptosis Regulation In Lung Cancermentioning
confidence: 99%